2006
DOI: 10.1002/pssb.200672585
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of single‐walled carbon nanotubes at high pressure: Effect of interactions between the nanotubes and pressure transmitting media

Abstract: We have studied single-walled carbon nanotubes (SWNT) at high pressure using Raman spectroscopy, in a variety of common solvents as hydrostatic pressure-transmitting media. We find that the response of the Raman G-band to high pressure varies significantly with choice of solvent. In particular, with hexane we observe a new irreversible effect -a flat Raman response to 0.7 GPa. We draw tentative conclusions from this work -that the solvents used can penetrate the interstitial spaces between nanotubes in a bundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…11,22 Many experimental studies have suggested that phase transition in nanotubes could be dependent on their metallic character or on the surrounding chemical environment used for transmitting the pressure. 4, [23][24][25][26] However, theoretical calculations suggest that phase transitions of SWNTs under pressure is mainly dependent on the cube inverted diameter (p c ∼ d −3 t ) of the tubes and not on the chirality. 11,27 Even if there is a huge dispersion of results concerning the pressure transition values from theoretical models, there is an overall agreement between different calculations on the existence of two phase transitions (circular-oval and oval-peanut) and that the critical pressures for those transitions are diameter dependent.…”
Section: Introductionmentioning
confidence: 99%
“…11,22 Many experimental studies have suggested that phase transition in nanotubes could be dependent on their metallic character or on the surrounding chemical environment used for transmitting the pressure. 4, [23][24][25][26] However, theoretical calculations suggest that phase transitions of SWNTs under pressure is mainly dependent on the cube inverted diameter (p c ∼ d −3 t ) of the tubes and not on the chirality. 11,27 Even if there is a huge dispersion of results concerning the pressure transition values from theoretical models, there is an overall agreement between different calculations on the existence of two phase transitions (circular-oval and oval-peanut) and that the critical pressures for those transitions are diameter dependent.…”
Section: Introductionmentioning
confidence: 99%
“…However, Sood et al 7 did observe a transition to graphite‐like behaviour at about 10 GPa, but their data did not show an unambiguous higher pressure shift than the graphite value at lower pressures. We reported solvent‐dependent plateaux using hexane and butanol as solvents, in which the Raman mode did not shift significantly until pressures of 0.4 and 0.7 GPa, respectively 8, 9. Yao et al 10 observed a plateau at a much higher pressure (8 GPa) in argon.…”
Section: Introductionmentioning
confidence: 84%
“…We reported solvent-dependent plateaux using hexane and butanol as solvents, in which the Raman mode did not shift significantly until pressures of 0.4 and 0.7 GPa, respectively. [8,9] Yao et al [10] observed a plateau at a much higher pressure (8 GPa) in argon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SWCNTs show extraordinary strength along the axial direction with a commonly accepted axial Young’s modulus value of ∼1 TPa. , Radial and axial deformations of SWCNTs has attracted much attention as it is possible to influence their structural and electronic properties. The deformation of large diameter SWCNTs under pressure to interacting elliptic-, racetrack-, and peanut-shaped cross sections have been reported both experimentally , and theoretically. , The structural changes of large diameter nanotubes have also been observed indirectly using Raman spectroscopy and directly using x-ray and neutron diffraction experiments. The application of pressure on single-walled carbon nanotubes has brought to light a number of interesting properties such as metal−insulator transitions .…”
mentioning
confidence: 99%